Faktor-faktor yang Mempengaruhi Partisipasi Mahasiswa dalam Proses Tutorial pada Metode Belajar Problem-Based Learning (PBL) di Fakultas Kedokteran Universitas Riau - M Yulis Hamidy; Enikarmila Asni (Jurnal Ilmu Kedokteran, 2010)
Problem-based Learning (PBL) is an effective approach to promote student-centered learning. PBL tutorials were thekey step in PBL process. Students’ participation in PBL tutorials can be influenced by many factors. The aim of thisstudy was to identify the factors that influence students’ participation in PBL tutorials among students in Faculty ofMedicine University of Riau. The research was a cross sectional study using self report questionnaires obtained fromPBL students, conducted in April - October 2009. The students’ participation was assessed using Visschers-Pleijersquestionnaires. The result revealed the characteristics of parcipants which are female (79.5%), 19 years old (40.2%),had GPA 2.50 – 3.00 (56.7%), had past experience in organization (89.0%). Among 44.1% of the participants showedactive participation in tutorial processs. Male students more likely active than female students (P = 0.045). Anotherfactors including age, GPA, past experience in organization, role of tutors, and quality of scenario were not influencedthe participation of subject. Students’ participation in PBL tutorials among students in Faculty of Medicine Universityof Riau was influenced by sex.